Seasonality in cowpea prices: effect of technology in Ekiti State, Nigeria (2007)
The study, Seasonality in Cowpea Prices: Effect of Technology in Ekiti State, was done to actually know the impact of technology in stabilizing the prices of cowpea in off- season and on-season from the first quarter of 1992 to the fourth quarter of 2002. It was found out that the people of Ekiti State consumed or demanded for higher quantities of cowpea during the second and fourth quarters of each year examined for the study. These two quarters were seen to be the harvesting and sales periods of the red or brown beans, and this also coincided with quarters of lower prices of the cowpea. The vector error correction result showed that among all the variables used, only the cost of applying' technology (i.e. cost of the use of fertilizers, herbicides, pesticides, storage devices and transportation) was significant, and should have impacted a great influence in stabilizing the seasonal prices of cowpea but this was not the case as rightly shown by coefficient of the error correction, 0.3 85456, which is positive (wrongly signed) and fairly low. It follows that from the findings that only a few farmers and wholesalers of cowpea applied technologies to improve the shelf lives of their products, and therefore cannot influence the market price of cowpea. The state and local Governments of Ekiti State should put in place policies and structures like good road networks within the state, affordability and availability of agricultural pesticides and herbicides, improvement on the available agricultural storage facilities, building of more modern storage facilities, and buying of excess agricultural produces in the on-season to release them in the open market during the off-season in other to stabilize prices at all seasons, as well as, to reduce the loses to the farmers and marketers.